Analisis Proksimat dan Karakteristik Fisik Beras Analog Berbasis Tepung Sukun dengan Penambahan Ikan Teri Nasi: Proximate Analysis and Physical Characteristics of Analogue Rice Based on Breadfruit Flour and Anchovy - Pujiastuti, Veronica Ima; Lubijarsih, Maria Amrijati; Febriani, Dita Hanna (Universitas Airlangga, 2025)
Background: Rice serves as a fundamental dietary component for Indonesians, therefore several complete high-nutrition analogue rice developed. The composite flour used in this study is based on breadfruit flour, with the addition of anchovies to enhance the nutritional content in the formula. Objectives: To determine the chemical and physical characteristics of analogue rice based on breadfruit flour and anchovies. Methods: Experimental research with a one-factor Completely Randomized Design (CRD). Four treatments consisted of (0%, 2.5%, 5%, and 7.5%) addition of anchovies in analogue rice formula and three replication treatments. Chemical tests consisting of water, ash, fat, protein, and carbohydrate content. Physical tests included rice density, cooking time, water holding capacity (WHC), 1000 grain weight, and hardness level. Data analysis was performed using the Analysis of Variance (ANOVA) and Post Hoc Duncan Multiple Range Test (DMRT). Results: Anchovies improve ash and protein, decrease fat and are not significantly different to carbohydrate and energy compared to the control. Analogue rice contained 4.94-8.41% protein. The water content meets the Indonesian National Standard (SNI) with a maximum limit of 14%. This study's formulation reduced WHC and increased bulk density. Cooking time, 1000 grain weight, and hardness level were not different compared to the control. The cooking time of analogue rice ranged from 15-16 minutes, and the weight of 1000 grains ranged from 16.33-17.57 g. Conclusions: Anchovies in the analogue rice formula result in higher protein, lower fat, and carbohydrates compared to the control. The moisture content of the analogue rice meets SNI.